NILAI-NILAI PANCASILA DALAM TRADISI KENDURI SEBAGAI SARANA MEMPERKUAT SOLIDARITAS ANTAR UMAT BERAGAMA - Nugeraheni, Risma Ananda; Lattu, Izak Y.M; Suwarto, Suwarto; Tampake , Tony (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This study focuses on the Kenduri tradition in Serang Village, at the foothills of Mount Slamet, Purbalingga, Indonesia, as an effort to strengthen interfaith community solidarity. The research addresses the issue of intolerance and religion-based conflicts that contradict Pancasila's values. The study aims to analyze how the Kenduri tradition contributes to the implementation of Pancasila values in community life. The research employs a qualitative method with a realist ethnographic approach. Data were collected through direct observations of the Kenduri tradition and virtual interviews with residents. Secondary data were sourced from relevant literature. The analysis connects field findings with theories of interreligious engagement (Izak Lattu), social solidarity (Emile Durkheim), and religiosity (John Titaley). The findings reveal that the Kenduri tradition reflects Pancasila values, including divinity through interfaith collective prayers, humanity through equality and empathy, unity through interfaith cooperation, democracy through deliberation, and justice through equitable roles and benefits. This tradition strengthens mechanical solidarity through shared occupations and organic solidarity through the division of labour. In conclusion, the Kenduri tradition effectively enhances interfaith community solidarity in the foothills of Mount Slamet, supporting Pancasila's goal of fostering harmony. The study recommends preserving local traditions as a means to build solidarity within multicultural communities.